"One does not say Moien, one has to say Bonjour": Expressing Language Ideologies through Shifting Stances in Spontaneous Workplace Interactions in Luxembourg. (August 2016) - Franziskus, Anne
Abstract : Drawing on both a language ideological framework and the concept of stancetaking (Jaffe 2009), this article analyzes how different language ideologies are constructed, shared, contested and reproduced in spontaneous interactions in multilingual Luxembourg. The analysis focuses on two conversations recorded in two multilingual workplaces in Luxembourg. In the first one, staff members from an IT company discuss the status of written Luxembourgish. In the second, several employees from a supermarket debate the appropriateness of different greeting routines in the local context. In both of these interactions, participants take up different stances towards Luxembourgish as a legitimate code and towards monolingual ideologies. The findings show that the different stance‐taking moves of the participants reflect their positions as either 'insiders' or 'outsiders' to this ideologically charged setting and are reminiscent of some broader societal stances in relation to language. The findings highlight three positions in particular: There is the long‐term resident who alternately takes an expert stance towards the local language and distancing himself from it to create solidarity with his work colleagues. Then there is the cross‐border worker, a relative newcomer, who is still in the process of 'making his way' into the sociolinguistic context by adopting greeting routines. And finally, there is the young Luxembourger whose stances are reminiscent both of the need for the local population to adjust to an increased number of newcomers and their sometimes conflicting ideological stances and of the generational shift in the use of Luxembourgish.